Residual stress determination by blind hole drilling and local displacement mapping in aluminium alloy aerospace components - Sviatoslav Eleonsky; Vladimir Pisarev; Eugene Statnik; Alexey Salimon; Alexander Korsunsky (Fracture and Structural Integrity)
The determination of residual stresses by combining blind hole drilling and optical interferometric measurement of relief deformation is re-visited to evaluate its applicability to aerospace structures. The experimental methodology involves drilling a deep blind hole and evaluating the hole diameter increments in the principal strain directions using electronic speckle-pattern interferometry (ESPI). This is followed by the determination of the principal residual stress components via the solution of the inverse correlation problem. The study presents the pathway to overcoming one of the primary obstacles in residual stress determination, namely, the optimization of the measurement and interpretation procedures to obtain reliable results. It can be concluded from the analysis of the problem that the formulae connecting the raw experimental data and to the sought residual stress component values lead to a well-posed inverse problem. This makes it possible to obtain estimations of the measurement uncertainty. High density fringe patterns from ESPI provide a rapid and reliable method for residual stress determination, as illustrated using examples of approximately 160 MPa stresses in irregular zones of thick-walled structures.